2013
DOI: 10.1111/jar.12056
|View full text |Cite
|
Sign up to set email alerts
|

Adapted Physical Activity Programme and Self‐Perception in Obese Adolescents with Intellectual Disability: Between Morphological Awareness and Positive Illusory Bias

Abstract: This study confirms the interest of weight management programmes for adolescents with intellectual disability and points to the need to take positive illusory bias more fully into account in the study of self-perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 47 publications
(89 reference statements)
1
22
1
Order By: Relevance
“…Examination of these interventions included assessing the effectiveness to promote positive change in body weight and composition as well as in secondary health-related outcomes. Overall, findings from this review indicate that interventions aimed at youth with ID have the propensity to foster positive anthropometric change by reducing fat mass (Elmahgoub et al, 2011;Ordonez et al, 2006;Salaun et al, 2014), BMI (Elmahgoub et al, 2009;Elmahgoub et al, 2011), WC (Elmahgoub et al, 2009;Salaun et al, 2014), and weight (Elmahgoub et al, 2009;Ordonez et al, 2006;Ptomey et al, 2015). Positive improvements to these anthropometric outcomes through behavior and lifestyle interventions is consistent with previous literature reviews of adult populations with ID as well as youth without an ID (Heller et al, 2011;Oude et al, 2009;Spanos et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Examination of these interventions included assessing the effectiveness to promote positive change in body weight and composition as well as in secondary health-related outcomes. Overall, findings from this review indicate that interventions aimed at youth with ID have the propensity to foster positive anthropometric change by reducing fat mass (Elmahgoub et al, 2011;Ordonez et al, 2006;Salaun et al, 2014), BMI (Elmahgoub et al, 2009;Elmahgoub et al, 2011), WC (Elmahgoub et al, 2009;Salaun et al, 2014), and weight (Elmahgoub et al, 2009;Ordonez et al, 2006;Ptomey et al, 2015). Positive improvements to these anthropometric outcomes through behavior and lifestyle interventions is consistent with previous literature reviews of adult populations with ID as well as youth without an ID (Heller et al, 2011;Oude et al, 2009;Spanos et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Results of secondary outcomes indicated positive trends in cardiometabolic variables (SBP, DBP, Tri, and Chl) but only DBP was significant at the group level in Tx arm. Salaun et al (2014) implemented a 9-month PA program utilizing a combination of aerobic and strength training exercises. A total of 23 participants between 6 years and 18 years with an ID classification of mild were included in the study.…”
Section: Resultsmentioning
confidence: 99%
“…Barriers include lack of understanding of consequences for choices or overestimation of actual health status for all ages in this group (Brehmer-Rinderer, Zigrovic, & Weber, 2014). Similarly, implementation of acquired knowledge by the individuals with ID is made more complex by the tendency of those individuals to overestimate their own competence (Salaun, Reynes, & Berthouze-Aranda, 2014). Existence of diminished motor capabilities is also problematic for some, as it affects participation in physical activity (Rimmer et al, 2010).…”
Section: Barriers To Knowledge and Skill Acquisitionmentioning
confidence: 99%
“…The relationship between self‐perception variables and morphological variables was examined by Salaun, Reynes, and Berthouze‐Aranda (). They found that global self‐esteem and self‐perception could predict the inclination towards a positive illusory bias, among adolescents ( n = 23) with obesity and intellectual disabilities that were scheduled to receive an intervention.…”
Section: Resultsmentioning
confidence: 99%